Consumption and Wage Inequality in the US: The Dynamics of the Last Three Decades. (21st May 2020) - Amin‐Smith, Neil; Attanasio, Orazio P.
Abstract: In this paper, we look at the evolution of consumption and wage inequality from 1980 to 2016 in the US. We use data from the Consumer Expenditure Survey (CEX) and the Current Population Survey (CPS) to look at differences in consumption and wages across groups in the population defined by educational attainment of the household head and year‐of‐birth cohort. We show that the results obtained by Attanasio and Davis (1996) for non‐durable consumption still hold in more recent decades. In addition to non‐durable consumption and services, we look at inequality measured in terms of expenditure on and stock of vehicles. The advantages of looking at these measures are that information on cars is typically measured more accurately than other components of expenditure and consumers are more likely to react by adjusting their stock of vehicles on the basis of long‐term expectations about their economic prospects.